Health-related quality of life and related factors among pregnant women - Fatemeh Estebsari; Zahra Rahimi Khalifeh Kandi; Farideh Jalili Bahabadi; Zahra Raiesi Filabadi; Kimia Estebsari; Davoud Mostafaei (Wolters Kluwer Medknow Publications, 2020)
CONTEXT: Quality of life is significant in all stages of life, including within pregnancy. The hormonal, emotional, psychological, and physical factors specific to pregnancy can affect and threaten the quality of life of pregnant mothers. AIMS: This study sought to investigate the health-related quality of life (HRQoL) and related factors among pregnant women SETTINGS AND DESIGN: This cross-sectional study was performed on 300 pregnant women who were in the second and third trimesters of pregnancy without any risk of high-risk pregnancy covered by a community health center in Yazd, Iran, between 2018 and 2019. SUBJECTS AND METHODS: The required data were collected using demographic questionnaire and HRQoL (SF-12v2) questionnaire STATISTICAL ANALYSIS USED: Data were analyzed using SPSS 18 software and ANOVA statistical tests (P < 0.05). RESULTS: Physical dimension of quality of life of pregnant women had the mean and standard deviation of 43.7 ± 7.3 and that psychological dimension had the mean and standard deviation of 31.5 ± 11.8. Physical dimension of quality of life was significantly correlated with maternal age, gestational age, body mass index before 12 weeks of pregnancy, mother's education and job as well as spouse's level of education (P < 0.05). Furthermore, the psychological dimension of quality of life was significantly correlated with gestational age, mother's education and occupation as well as spouse's level of education (P < 0.05). CONCLUSIONS: According to the findings, attention to physical and psychological aspects of quality of life of pregnant women and demographic factors affecting it is essential for improving maternal and child health during and after pregnancy.